PENGEMBANGAN MEDIA POP UP BOOK MATERI SIKLUS HIDUP HEWAN KELAS IV DI MI HAMKA MUHAMMADIYAH KALIBEBER WONOSOBO - Novia Ayudya Anggraeny; Sholehuddin Sholehuddin (Jurnal Holistika, 2023)
The development of Pop Up Book media for animal life cycle material for class IV at MI Hamka Muhammadiyah Kalibeber, Mojotengah, Wonosobo is a research that is motivated by the limited learning media used by educators during the learning process and the lack of focus of students in participating in learning activities. The purpose of the research is to find out the development of pop up book media on the animal life cycle, and to assist educators in using learning media, so that students feel that learning is fun and not boring. The research method used is Research and Development (RnD) using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. This study used a population of 21 people, with a sample of 19 people. The data sources used in the development of this learning media are in the form of expert validation assessment instruments by linguists, material experts and media experts and student practicality questionnaires through two stages of trials consisting of small group trials and large group trials. The results of this study indicate that the validation test reaches a validity level of 98%, the material validation test reaches a validity level of 78%, and the media validation test reaches a validity level of 88%. The small group practicality test reached 92.8% and the large group practicality test reached 90%. Based on these results, the learning media can be used as learning media. The results of the research are expected to provide benefits to related parties as educators, students, and further researchers.